2022
DOI: 10.3390/pharmaceutics14081699
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Laser Scanning Microscopy and Model Membranes to Study Translocation Mechanisms of Membrane Active Peptides

Abstract: Membrane active peptides hold great potential for targeted drug delivery systems and understanding their mechanism of uptake is a key step in the development of peptide based therapeutics and clinical use. Giant unilamellar vesicles are cell-sized model membranes that can be individually observed under the microscope. The lipid composition of these membranes can be controlled, and interaction with peptides and changes induced by the peptides can be directly followed. Relevant information on the specific steps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We previously demonstrated that interaction of peptides with membranes and their translocation efficiency depend on lipid composition [32,33,34] . The lipid head group charge and lipid topology are the main driving factors for the interaction and permeability of TAT peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that interaction of peptides with membranes and their translocation efficiency depend on lipid composition [32,33,34] . The lipid head group charge and lipid topology are the main driving factors for the interaction and permeability of TAT peptides.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that interaction of peptides with membranes and their translocation efficiency depend on lipid composition. [32,33,34] The lipid head group charge and lipid topology are the main driving factors for the interaction and permeability of TAT peptides. Also, we have established that the hydrophobic lipid tails, either saturated or unsaturated (with cis-double bonds) do not influence the activity of the peptides.…”
Section: Penetrating Properties Of the Rgdà Tat Peptidementioning
confidence: 99%
“…Among these techniques, two commonly utilized methods include laser scanning confocal fluorescence microscopy (LSCFM) and total internal reflection fluorescence microscopy (TIRFM). LSCFM, known for its high resolution, optical sectioning, and 3D imaging capabilities [ 79 , 80 ], serves to characterize liposomes and observe their structure, behavior, and interactions with high precision [ 81 , 82 ]. In contrast, TIRFM is well-known for its accessibility and high sensitivity in probing biomolecules properties [ 83 ].…”
Section: Characterization and Major Components Of Liposomesmentioning
confidence: 99%